2003
DOI: 10.1038/sj.leu.2402932
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of elderly patients (≥60 years) with newly diagnosed acute promyelocytic leukemia. Results of the Italian multicenter group GIMEMA with ATRA and idarubicin (AIDA) protocols

Abstract: In all, 134 elderly patients (median age 66 years, range 60-75 years) with newly diagnosed acute promyelocytic leukemia (APL) were enrolled in two successive protocols of the Italian multicenter group GIMEMA. All patients received an identical induction with all-trans retinoic acid and idarubicin; 116 (86%) entered complete remission (CR), two (2%) were resistant and 16 (12%) died during induction. After CR, 106 patients received further therapy whereas 10 did not, because of refusal (n ¼ 5) or toxicity (n ¼ 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 24 publications
(23 reference statements)
5
49
2
Order By: Relevance
“…Similar findings were made by the Italian GIMEMA study, where 86% of the patients older than 60 years with newly diagnosed APL treated with ATRA and idarubicin achieved complete remission and 12% died during induction, mainly from hemorrhage, ATRA syndrome, sepsis or heart failure. 8 A lower CR rate in elderly patients was also found by the Spanish PETHEMA and the Japanese groups with ATRA combined to or followed by chemotherapy, but data in those two studies were only available for patients older than 70 3-5 ( Table 2). As in the present study, the difference with younger adults was due to a higher incidence of early deaths, generally secondary to bleeding or sepsis.…”
Section: Response To Induction Treatmentmentioning
confidence: 95%
See 3 more Smart Citations
“…Similar findings were made by the Italian GIMEMA study, where 86% of the patients older than 60 years with newly diagnosed APL treated with ATRA and idarubicin achieved complete remission and 12% died during induction, mainly from hemorrhage, ATRA syndrome, sepsis or heart failure. 8 A lower CR rate in elderly patients was also found by the Spanish PETHEMA and the Japanese groups with ATRA combined to or followed by chemotherapy, but data in those two studies were only available for patients older than 70 3-5 ( Table 2). As in the present study, the difference with younger adults was due to a higher incidence of early deaths, generally secondary to bleeding or sepsis.…”
Section: Response To Induction Treatmentmentioning
confidence: 95%
“…For example in the GIMEMA study, a 13% incidence of deaths in CR were seen in patients who received three consolidation chemotherapy courses vs 5% in patient who received one consolidation course. 8 Reduction in mortality can also be obtained by avoiding the use of Ara C in the chemotherapy regimen, as shown by the Spanish PETHEMA group 4,5 and also by other studies. 14 Early introduction of arsenical compounds like As 3 O 3 15 or As 4 S 4 , 16 which have no myelosuppressive effect, during induction or consolidation treatment, could also allow reduction of the total amount of chemotherapy administered in elderly APL patients.…”
Section: Response To Induction Treatmentmentioning
confidence: 96%
See 2 more Smart Citations
“…It has been suggested that a reduction in the intensity of consolidation in older adults may be beneficial. 25 …”
Section: Prognostic Factors Predicting For Early Deathmentioning
confidence: 99%